Устройство для моделирования трехфазной линии электропередачи с сосредоточенными параметрами - Боровиков Ю. С. Юрий Сергеевич; Сулайманов А. О. Алмаз Омурзакович; Рубан Н. Ю. Николай Юрьевич; Гусев А. С. Александр Сергеевич; Прутик А. Ф. Алексей Фёдорович; Андреев М. В. Михаил Владимирович
опубл. 10.12.12